Functional Strategy Comparison Between Startup and Established Companies on 'Konveksi' and 'Sablon' Business in Bandung - Aziiz, Muhammad Fattah; Dhewanto, Wawan (Journal of Business and Management, 2015)
Abstract - Ã¢â‚¬ËœKonveksiÃ¢â‚¬â„¢ and Ã¢â‚¬ËœSablonÃ¢â‚¬â„¢ services is one of the types of businesses that grow and spread in Bandung city. Popularity on this business primarily due to two things. First, because the products produced by this industry, namely clothing is one of the basic human needs, so the market for this business will always exist. Second, this business became popular because the entry barrier to start the business is not too big. Most of these companies have similar business strategy and provide same kind of services. With big potential market and potential profits, many businessman now want to starts this business. Because of that, the competition in this kind of business increase more rapidly in Bandung. Against the competition, those companies need to use better functional strategy. Functional strategy helps smaller businesses to evaluate the effects of plans and goals specific to the industry they operate within. This paper is made to determine how the application of functional strategy in Ã¢â‚¬ËœkonveksiÃ¢â‚¬â„¢ and Ã¢â‚¬ËœsablonÃ¢â‚¬â„¢ business in order to survive in the competition and develop their business in Bandung. Comparison also will be made to determine the similarities and differences of functional strategy between startup (less than 5 years) and established company (more than 5 years). After determine the research problem and research questions, exploratory research is used to gain a deeper understanding of the issue or situation. In this research the exploratory research are relies on literature review, observations, and in-depth interview. Purposive and snowball sampling is used to determine the key informants of this research. The result from comparisons shown that in general, startup and established company have same opportunity and face same threat in the industry. Therefore, established company have more advantages (strength) compare to startup company. Comparison about the functional strategy also shown that there are 9 similarities and 6 differences strategy. For the similarities, most of these companies have undifferentiated (mass market) target market, used cost based pricing, provide almost same variant products, mostly made periodic financial report, mostly divided profits into several posts, mostly already have rules or SOPs, mostly chose to loyal at specific supplier, performed maintenance periodically, and most employees being paid based on project. For the differences, some startup companies advance in technology (using website and BBM broadcasting message) for their promotion while established companies mostly depends on conventional marketing via word of mouth. Second, most of startup companies have financial problem for developing their business, while the established companies have no financial problem for their improvement. Third, most of startup companies have small production capacity due to their limited resources, while most of the established companies have large production capacity. Most of startup recruit skilled and experienced people for their employees, while most of established companies chose to recruit people with less / have no skill and have no experience in the industry then trained them. Most of startup companies have employees less than 10 people, while most established companies have more than 10 employees. Then, startup companies usually still have lack on internal control that make turnover employees happened many times, while the established companies have employees with high loyalty.Ã‚Â For recommendations, all owner of Ã¢â‚¬ËœkonveksiÃ¢â‚¬â„¢ and Ã¢â‚¬ËœsablonÃ¢â‚¬â„¢ business in Bandung should pay more attention on the functional strategy application, think about some innovations, and follow the advances in technology to stand in the competition. Then, always try to understand the potential market and calculate the potential customers to build the right size of the company.Ã‚Â Keywords: Functional Strategy Comparison, Ã¢â‚¬ËœKonveksiÃ¢â‚¬â„¢ and Ã¢â‚¬ËœSablonÃ¢â‚¬â„¢ Business, Start Up and Established CompaniesÃ‚Â